INCREASING STUDENTS ATTENTION TO THE INDONESIAN LANGUAGE LEARNING PROCESS THROUGH ICE BREAKING IN CLASS IV - Wilda Maulidiyah Saniyah; Rika Mellyaning Khoiriya (maktab: Jurnal Pendidikan dan Teknologi, 2022)
This article discusses the classroom action research that has been carried out regarding increasing students' attention to the Indonesian language learning process through ice breaking. This research was conducted because there were problems in learning in class IV SDN Boro, namely many students were chatting and playing alone instead of paying attention to the teacher explaining the material or friends during presentations. The purpose of this research is to increase students' attention through ice breaking in the Indonesian language learning process. This research was conducted from pre-cycle, cycle I, to cycle II. In the pre-cycle, data were taken from the results of observations, interviews, and questionnaires. While in cycles I and II, the data were obtained from observations and questionnaires. The results showed that the attention of students can be increased by the presence of ice breaking in learning activities. This can be seen from the average attention score obtained by students in the initial observation (pre-cycle) which is 51.3 in the medium category, then the average attention score increases in the first cycle which is 72.3 in the high category, and increased higher in the second cycle that is equal to 82.3 with a very high category and students who get a score of 70 are as many as 20 students (91%). This research should be a reference for solving problems related to the lack of attention of students in the Indonesian language learning process so as to improve the quality of learning.